Lembaga Pendidikan Islam (Pondok Pesantren, Pendidikan Diniyah, Formal, Kelompok Belajar Masyarakat, Madrasah, dan Home Schooling) - Reni Septiana; Imam Maliki; Mohamad Yahya Ashari (Indo Publishing, 2026)
Islamic educational institutions play a strategic role in shaping generations who are not only intellectually competent but also possess strong religious character and competitiveness in the era of globalization. This study aims to analyze the types of Islamic educational institutions, examine their existence and roles in the globalization era, explain the importance of institutional transformation, and formulate management development strategies for highly competitive Islamic educational institutions. This research employs a qualitative approach using a library research method, data analysis is conducted through content analysis with a descriptive-analytical approach. The findings indicate that Islamic educational institutions consist of various forms, including Islamic boarding schools (pesantren), madrasahs (formal education), diniyah education (non-formal), community learning groups, and Islamic homeschooling (informal). Each type has distinct characteristics and complementary roles in meeting the educational needs of society. In the era of globalization, Islamic educational institutions remain relevant and play significant roles as centers for character building, preservation of Islamic values, and community empowerment. However, the challenges of globalization require transformation in curriculum development, digitalization of learning, instructional methods, and institutional management. Effective management development strategies such as improving human resources quality, curriculum innovation, implementation of quality-based management, strengthening collaboration, and educational digitalization are essential to enhance institutional competitiveness. With appropriate transformation and sustainable management strategies, Islamic educational institutions have strong potential to contribute to the development of a modern civilization grounded in Islamic values.